GEOCHEMICAL CHARACTERISTICS OF HOT SPRINGS IN BATU LEPOQ AND PANGADAN VILLAGES, KARANGAN DISTRICT, EAST KUTAI REGENCY, EAST KALIMANTAN PROVINCE - Habibah, Miftah Faaza; Putri, Resty Intan; Sabrian, Panggea Ghiyats; Shoedarto, Riostantieka Mayandari; Saepuloh, Asep (Universitas Mulawarman, 2023)
The Karangan District in East Kutai Regency, East Kalimantan Province, is identified as having geothermal potential in the villages of Batu Lepoq and Pangadan. The presence of hot springs in these locations underscores the area's rich geological features, despite the absence of active volcanoes on the island. This study aims to analyze the physical and geochemical characteristics of the hot springs. A conceptual model of the geothermal system was developed to evaluate the geothermal potential of the area. Geochemical data from field samples were analyzed using geochemical methods. The findings indicate that the equilibrium lies in the immature water zone, with the primary source of the hot fluid being meteoric water heated by geopressure. The temperature of the sole reservoir in the Pangadan Village geothermal system is estimated to be 1930±10°C, as determined by the 1988 Giggenbach geothermometer.